Views of Fiqh Sosial on Cooperation in the Construction of Inter-Religious Houses of Worship - Khabib Solihin; Siti Asiyah (Santri: Journal of Pesantren and Fiqh Sosial, 2021)
There is an interesting phenomenon that occurs in the Village of Tunahan, Keling, Jepara is a collaboration carried out by interfaith communities in building houses of worship. This phenomenon is very interesting to study using the point of view of Fiqh Sosial in accordance with the spirit of maqashid sharia and the benefit it carries in its methodology. This research is a qualitative research that leads to the study of a natural case that occurs in the community, namely the cooperation in the construction of places of worship between religions which is carried out alternately, the results of this research are carried out descriptively verification. From the results of the analysis carried out, this study produces several conclusions. First, the cooperation in building houses of worship between religions in Tunahan Village is a manifestation of human manifestation as social beings who have a natural need for each other. Second, in the concept of Fiqh Sosial, cooperation in the construction of places of worship between religions in Tunahan Village is a form of the implementation of human duties to prosper the earth which is oriented towards harmony and brotherhood so as to increase better religious activities. Third, seeing the many cases of religious intolerance that still occur in this country, religious harmony is one of the basic human needs (dharuriyyah) that must be realized through various actions.